Overview of underground coal gasification operations at Chinchilla, Australia. Issue 24 (16th December 2016) - Perkins, Greg; du Toit, Ernest; Cochrane, Greg; Bollaert, Grant
ABSTRACT: Underground coal gasification (UCG) is a process which converts deep, un-mineable or difficult to mine coal resources into syngas which can then be converted into valuable end products such as electric power, liquid fuels, synthetic natural gas and chemicals. This paper provides a summary of the UCG operations conducted at the Chinchilla Demonstration Facility in Australia, focusing on gasifiers constructed using directional drilling. A number of the experiences and key lessons learned from operating multiple underground gasifiers over several years at the facility are described. Implications for the implementation in commercial projects using UCG are also discussed. Finally, the potential of UCG as a method for producing syngas from deep coal is discussed and some of the challenges and opportunities are summarized.